(3cJGH aj GdCUhds ((3eMeO Hf MSjf GdOhQSi GdTGaYi s)
(3ChdgG (B:s
(3Pdc ajg hgh TQW jMbb GdGfJgGc dGfJaGA TQWg aJfai GdYbhHI s
(3BNQgG (B:s
(3hef LgI eG jbY ai faS GdCeQ GdMOhO ef eaQOGJg Ke QcHJ HYVgG MUd CehQ dGJcGO JfMUQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3CUhd Gdabgs